Pendampingan Jaringan Komunitas dalam Pengembangan Wahana Belajar Masyarakat di Desa Kedungglugu Kecamatan Gondang Kabupaten Nganjuk - Ma’sum, Toha (Janaka, Jurnal Pengabdian Masyarakat, 2019)
Community empowerment in the era of globalization requires the involvement of universities to carry out social transformation. Social transformation can be done by making the community a social laboratory to bring about change. The religious, economic and social community in Gedungglugu Gondang Nganjuk which is the subject of assistance from STAI Darussalam shows a willingness to mobilize its assets and potential to be empowered. Through the assistance program with the ABCD approach, the three communities were given stimulation to build networks in order to solve the problems they faced. The apparent result of the assistance is the building of social philanthropy so as to facilitate social solidarity. The building of social solidarity is proven to be able to encourage the three assisted communities to realize activities independently and sustainably.